The Effect of Leadership Style and Work Environment on Employee Performance at Alila Ubud - Pradnya W, Desak Made Chintya Mahadewi; Sihombing, Irene Hanna H.; Sabudi, I Nyoman Sukana (PT FORMOSA CENDEKIA GLOBAL, 2024)
Hotels are able to significantly increase profits by optimizing the capacity of human resources (HR). Poor employee performance has a negative impact on the company, including laziness in completing work, lack of work achievement, and employee discipline. This study has a mission to assess the impact of leadership style and work environment on employee performance at Alila Ubud. This study used a qualitative approach with a saturated sampling technique, involving 120 respondents as the sample. Data was collected through surveys distributed to respondents. Data analysis was conducted using multiple linear regression methods, t-test, f-test, and coefficient of determination. The study results state that 64% of employee performance is driven by leadership style and work environment, while the remaining 31% is driven by other factors not analyzed in this study.